Therapeutic Communications of Doctors and Hypertensive Patients’ Satisfaction - Reka Elvia Dirda Prasasta; Linda Dewanti; Dominicus Husada; Lilik Djuari (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Highlights:1. Doctors who perform therapeutic communication make patients more satisfied with their services.2. Good therapeutic communication is the most effective way to establish relationships with patients with long-term treatment such as hypertension. AbstractIntroduction: Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg at two measurements at intervals of five minutes under adequate rest/calm conditions. Therapeutic communication is the most effective and important thing in establishing relationships between doctors and patients. Good communication based on trust will produce satisfaction from the patients, thus they can seek treatment again. This study aimed to analyze the relationship between therapeutic communication and hypertensive patients’ satisfaction measured among those who visited the Primary Health Center (PHC) of Surabaya to control their blood pressure.Methods: This was a cross-sectional quantitative study with all hypertensive patients who visited the PHC in November 2018-January 2019 as the subjects. Characteristics of the subjects, as well as the doctors and the therapeutic communication practices, were rated by the patients. Patients’ satisfaction was collected using validated questionnaires.Results: According to a relationship analysis between doctors’ therapeutic communication and patients’ satisfaction, it is found that there was a significant relationship. This was based on a significance value of 0.00 and smaller than 0.05. The better the communication applied by the doctor, the more satisfied the patient was. This study showed that service satisfaction was influenced by therapeutic communication where doctors at the PHC try to fulfill every indicator.Conclusion: There was a relationship between the therapeutic communication of doctors and the satisfaction of hypertensive patients at the PHC.